A multidisciplinary approach to severe bronchopulmonary dysplasia is associated with resolution of pulmonary hypertension - Yung, Delphine; Jackson, Emma O.; Blumenfeld, Alyssa; Redding, Gregory; DiGeronimo, Robert; McGuire, John K.; Riker, Meredith; Tressel, William; Berkelhamer, Sara; Eldredge, Laurie C. (Frontiers in Pediatrics, 2023)
OBJECTIVE: To describe our multidisciplinary bronchopulmonary dysplasia (BPD) consult team’s systematic approach to BPD associated pulmonary hypertension (PH), to report our center outcomes, and to evaluate clinical associations with outcomes. STUDY DESIGN: Retrospective cohort of 60 patients with BPD-PH who were referred to the Seattle Children’s Hospital BPD team from 2018-2020. Patients with critical congenital heart disease were excluded. Demographics, comorbidities, treatments, closure of hemodynamically relevant intracardiac shunts, and clinical outcomes including time to BPD-PH resolution were reviewed. RESULTS: Median gestational age of the 60 patients was 25 weeks (IQR: 24-26). 20% were small for gestational age (SGA), 65% were male, and 25% received a tracheostomy. With aggressive cardiopulmonary management including respiratory support optimization, patent ductus arteriosus (PDA) and atrial septal defect (ASD) closure (40% PDA, 5% ASD, 3% both), and limited use of pulmonary vasodilators (8%), all infants demonstrated resolution of PH during the follow-up period, including three (5%) who later died from non-BPD-PH morbidities. Neither SGA status nor the timing of PH diagnosis (< 36 versus ≥ 36 weeks PMA) impacted the time to BPD-PH resolution in our cohort (median 72 days (IQR 30.5-166.5)). CONCLUSION: Our multidisciplinary, systematic approach to BPD-PH management was associated with complete resolution of PH with lower mortality despite less sildenafil use than reported in comparable cohorts. Unique features of our approach included aggressive PDA and ASD device closure and rare initiation of sildenafil only after lack of BPD-PH improvement with respiratory support optimization and diagnostic confirmation by cardiac catheterization.